IMPLEMENTASI FATWA-FATWA DSN-MUI PADA PEMBIAYAAN DANA TALANGAN HAJI (STUDI KASUS PADA PADA KSPPS BTM MULIA BABAT – LAMONGAN) - Saidi, Ahmad Arif Rahman; warsidi, warsidi (Universitas Muhammadiyah Surabaya, 2020)
ABSTRACT The use of religious guidances from DSN-MUI as a basis of delivering products in the Micro-Sharia Financial Institution (LKS) is not accompanied by a complete and correct understanding of the implementation. It can be seen in among others, the fund financing of hajj bailout. There are many different kinds of contracts used by micro-sharia financial institution in the hajj bailout fund financing, such as the contract of qardh bil ujrah and ijarah multijasa, even there are those that uses murabahah contract in the hajj fund financing.The author's interest in examining the implementation of hajj bailout fund financing in KSPPS BTM Mulia is because the KSPPS BTM Mulia used the contract of qardh bil ujrah and then change it into ijarah multijasa at the beginning of the emergence of the product of hajj bailout fund financing. The author intends to find out about the implementation in KSPPS BTM Mulia, which contract is most in accordance with the Sharia economic law, and what are the impact of the changes for KSPPS BTM Mulia.This study is a qualitative-descriptive research which uses the data collection technique with observation, interview, and documentation. The data source of this study is: (1) the person who is involved in hajj fund financing in KSPPS BTM Mulia starting from the management, Sharia supervisory board, marketing, legal, and customers; and (2) contract documents, minutes of meetings, and other documents which related to and needed in this study.From this study, it is known that the implementation of hajj bailout fund financing in KSPPS BTM Mulia that uses the qardh bil ujrahcontract, the halal status cannot be guaranteed, while the ijarah multijasa contract with little improvement will be more appropriate and in accordance with the Islamic Sharia principles. Keywords :Hajj Bailout Fund Financing, Contract ofQardh ,Ijarah Multijasa, Kafalah